The Role of Information and Communication Technology in Corporate Communication Management - Wiwi Budiarti (Sean Institute, 2023)
In an ever-evolving digital era, companies increasingly recognize that ICT has a significant impact on the way they communicate with various stakeholders, including employees, customers, investors and society at large. This research aims to investigate the important role of Information and Communication Technology (ICT) in the context of corporate communication management. This research will use qualitative research methods with descriptive methods. The results of this research show that Information and Communication Technology (ICT) plays a crucial role in corporate communication management. ICT has changed the way companies communicate, making it easier to communicate internally and externally quickly and efficiently. In addition, ICT allows companies to monitor business developments in real-time, manage data efficiently, and improve operational efficiency, which can ultimately result in cost savings and increased profitability. In addition, the role of ICT in Customer Relationship Management (CRM) helps companies understand and meet customer needs, improve customer service, and build customer loyalty. Overall, ICT is an irreplaceable asset in improving company performance and growth.